An annotated list of the vascular plants recorded on territory of the regional landscape park “Kinburnska kosa” in 2007-2009 (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
An annotated list of the vascular plants recorded on territory of the regional landscape park “Kinburnska kosa” in 2007-2009 wich included 596 species of 313 genera, 83 families, 5 classis, 4 divisio are present. Among them 29 species included to the different Red List.
Keywords: flora, vascular plants, regional landscape park “Kinburnska kosa”, an annotated list.